Men spake from God studies in the Hebrew prophets - Ellison, Henry Leopold, 1903- (London, UK Paternoster, 1958)
Includes bibliographical references and index.
Brethren writer. Copy 1 donated by Mr J. Phillips, student, 1960. Copy 2 donated by Miss B. Brewer, student, 1960. First edition also held.
Keywords: Bible. O.T. Prophetic books -- commentaries